Digital Competence among Teacher Training Master’s Degree Students: Differences by Gender, Age, and Field of Study - Estibaliz Cepa-Rodríguez; Vanesa Lancha-Villamayor (Revista Latinoamericana de Tecnología Educativa)
Digital competence (DC) among education professionals is a very popular object of study in approaches oriented towards educational innovation. This study aims to analyse digital skills and relate them to sociodemographic characteristics in a sample of future teachers. Participants were 154 Teacher Training Master's Degree students. The Questionnaire for Studying the Digital Competence of Higher Education Students (CDAES) was used to measure DC. The results reveal that future teachers have a medium-low level in the different dimensions of DC. Specifically, they scored highly for basic tasks associated mainly with ‘Digital Literacy’, although shortcomings were observed in activities related to ‘Creativity and Innovation’ and ‘Critical Thinking’. The results also revealed that DC decreases as age increases, and that students coming from Social Science degrees had the lowest CD indexes, whereas those from Technology and the Natural Science had the highest scores. There is a need for DC training plans that include personalised innovative educational strategies, or in other words, strategies specifically adapted to the characteristics of different university degrees.